Fracture Surface Morphology of Delamination Failure of Polymer Fiber Composites Under Different Failure Modes - YAYLA, PAŞA (SPRINGER, 2016)
The delamination of fiber reinforced polymer composites is one of the most common failures encountered in industrial applications. The most unique macroscopic and microscopic fracture surface features of the delaminations under different failure modes are of interests not only for practical failure analysis investigations but also it helps to reveal the physics behind the delamination phenomenon. In this work, fracture surface morphology of the delaminated carbon fiber polymer composites under mode I, mode II, and mixed-mode I/II loading conditions is investigated mainly with scanning electron microscopy. The unique fractographic features are identified and discussed. The results on ductile and brittle matrix composites have shown their own features, and most important of all the alignment angle of fibrils in the resin-rich ductile matrix could be correlated with the delamination mode.
Keywords: Delamination; Fiber composites; Fractograph; Failure modes; REINFORCED THERMOPLASTICS; MATRIX FRACTOGRAPHY